2012
DOI: 10.1007/s13224-012-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Cell Proliferating Nuclear Antigen (PCNA) and p53 Protein in Cervical Cancer

Abstract: These markers may be of greater importance in low-grade CIN lesions showing high proliferative index. This will place the low-grade lesions in higher grade indicating the utility of proliferative markers in decision making for intervention. This method is simple and cost effective and may be useful in developing countries where HPVDNA testing is still out of reach because of high cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Microarray analysis also revealed that the genetic or pharmacological interference of p53 may directly affect SULF2 expression, and SULF2 was confirmed to be a novel transcription target of p53 (28). Notably, previous evidence has demonstrated a close association of the significant upregulation of p53 with the progression of cervical cancer (29,30). These findings may provide another possibility wherein the increased expression of SULF2 in cervical cancer might be partially induced by p53 upregulation.…”
Section: Discussionmentioning
confidence: 70%
“…Microarray analysis also revealed that the genetic or pharmacological interference of p53 may directly affect SULF2 expression, and SULF2 was confirmed to be a novel transcription target of p53 (28). Notably, previous evidence has demonstrated a close association of the significant upregulation of p53 with the progression of cervical cancer (29,30). These findings may provide another possibility wherein the increased expression of SULF2 in cervical cancer might be partially induced by p53 upregulation.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, the College of American Pathologists included p16 immunohistochemistry to categorize lower anogenital tract squamous lesions [18]. Proliferating cell nuclear antigen (PCNA) is essential for nucleic acid replication and repair machinery and used as a surrogate marker for cell proliferation [19]. Its expression has been associated with severity and progression of cervical neoplasia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant p53 is detectable by immunohistochemical methods, because of its stability and long half-life. Reports have revealed that the p53 gene has a low mutation rate, but a high level of positive expression in cervical cancer tissues (Madhumati et al, 2012). Positive p53 expression is not indicative of mutation, but of the inclination for mutation, with the cancer cells growing rapidly once a p53 mutation occurs.…”
Section: Discussionmentioning
confidence: 99%